Criminal justice trends: key legislative changes in sentencing policy, 2001-2010 - Adrienne Austin (My University, 2016)
Since 2001, many state legislatures have changed their criminal sentencing policies, increasingly emphasizing approaches that are “smart on crime.” The three main areas of legislative reform involve redefining and reclassifying criminal offenses, strengthening alternatives to incarceration, and reducing prison terms. This report is a reference for legislators, their staff, and other policy makers who may be considering or implementing similar changes in sentencing statutes and policies.